Privatisation of municipal golf courses in small towns in the Western Cape, South Africa. Issue 2 (4th May 2017) - Spocter, Manfred
Abstract: There has been a surge of interest by geographers in contemporary South African small towns. This paper reports on the sale of municipal land in small towns from 1974 to 2014 in selected municipalities of the Western Cape. Attention is focused on the sale of municipal golf courses as an example of privatized municipal land that has not contributed to undoing apartheid spatial legacies or integrating small-town communities. The rate of municipal land sales increased appreciably after the introduction of the neoliberal Growth Employment and Redistribution macro-economic strategy in South Africa. Neoliberal processes have adapted to local conditions and morphed into what is known as the Third Way: essentially a marriage between the neoliberal agenda and postapartheid egalitarian principles. The divisive nature of privatized, once municipally owned, spaces is supposed to be offset by investment in social development funds for some small towns. It is intended that these funds be managed by municipalities and spent on projects identified in the Integrated Development Plan. Documentation of environmental impact assessments of privatized golf courses provides insights into the logic of the privatization of small-town municipal golf courses and the addition of residential components to them. It is concluded that the secure, gated and fortified housing spaces of the golf estates are aimed at the monied classes and have become enclaves of wealth within the broader small-town milieu. The developmental dilemma is that while municipalities may benefit from such land sales and their subsequent revenues, socio-spatial integrative opportunities are being sacrificed for monetary gain.